2021
DOI: 10.1620/tjem.255.111
|View full text |Cite
|
Sign up to set email alerts
|

GINS Complex Subunit 2 Facilitates Gastric Adenocarcinoma Proliferation and Indicates Poor Prognosis

Abstract: Gastric cancer is the one of the most lethal malignancies of digestive system. Identifying molecular biomarkers is invaluable in help predicting clinical outcomes and developing targeted chemotherapies. GINS complex subunit 2 (GINS2) plays an essential role in the initiation and elongation of DNA replication. Although there have been studies revealing the prognostic significance of GINS2 in breast cancer and lung cancer, its involvement and function in gastric cancer need to be elucidated. We retrospectively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The results show that GINS2 expression is increased in most tumors compared to normal tissues and correlates with various clinicopathological features. It has been demonstrated that GINS2 is expressed at higher levels in tumor tissue than in adjacent normal tissue, such as in CC[ 3 ], gastric adenocarcinoma[ 6 ], glioma[ 7 ], NSCLC[ 8 , 9 ], pancreatic cancer[ 10 , 11 ], and thyroid cancer (TC)[ 12 , 13 ]. Specifically, analysis of potential correlations between GINS2 expression levels and clinicopathological features has indicated that high GINS2 expression levels are closely associated with tumor size[ 6 , 10 ], tumor nodal metastasis (TNM) stage[ 6 , 8 ], pathological grade[ 7 ] and vascular permeation[ 10 ].…”
Section: Expression Profiles Of Gins2 In Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that GINS2 expression is increased in most tumors compared to normal tissues and correlates with various clinicopathological features. It has been demonstrated that GINS2 is expressed at higher levels in tumor tissue than in adjacent normal tissue, such as in CC[ 3 ], gastric adenocarcinoma[ 6 ], glioma[ 7 ], NSCLC[ 8 , 9 ], pancreatic cancer[ 10 , 11 ], and thyroid cancer (TC)[ 12 , 13 ]. Specifically, analysis of potential correlations between GINS2 expression levels and clinicopathological features has indicated that high GINS2 expression levels are closely associated with tumor size[ 6 , 10 ], tumor nodal metastasis (TNM) stage[ 6 , 8 ], pathological grade[ 7 ] and vascular permeation[ 10 ].…”
Section: Expression Profiles Of Gins2 In Cancersmentioning
confidence: 99%
“…GINS2, also known as Psf2, is located in regions 2 and 4 of the long arm of chromosome 16 with a length of 1196 bp[ 2 ], as shown in Figure 1 . Recent results suggest that GINS2 expression is upregulated in many diseases, especially tumors, and adversely affects prognosis, such as in patients with cervical cancer (CC)[ 3 ], breast cancer (BC)[ 4 , 5 ], gastric adenocarcinoma[ 6 ], glioma[ 7 ], non-small cell lung cancer (NSCLC)[ 8 , 9 ], and pancreatic cancer[ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The TCGA database analysis revealed that all members of GINS were upregulated in LUAD tissues and their high expression predicted the prognosis of the patients. Several studies demonstrated that the expression of a GINS member enhanced cancer cell aggressiveness, e.g., proliferation, drug resistance, and epithelial-mesenchymal transition [55,59,60]. Therefore, GINS members are closely involved with LUAD pathogenesis and may be potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Among all gastric cancer cases, the majority of patients were diagnosed as stomach adenocarcinoma (STAD) arising from malignant change of gastric gland cells, accounting for 90–95% of total cases [ 2 ]. The causative factors of STAD are commonly attributed to environmental stimuli (mainly H. pylori infection) and genetic susceptibility [ 3 ]. Despite the availability of multidisciplinary combination therapy including surgery and chemotherapy for STAD patients in the past decades, clinical outcomes remain suboptimal and median survival time has not been effectively prolonged [ 4 ].…”
Section: Introductionmentioning
confidence: 99%